Morphological and Chemical Traits of Cladonia Respond to Multiple Environmental Factors in Acidic Dry Grasslands - Gabriele Gheza; Luca Di Nuzzo; Chiara Vallese; Matteo Barcella; Renato Benesperi; Paolo Giordani; Juri Nascimbene; Silvia Assini (Microorganisms, 2021)
Terricolous lichen communities in lowlands occur especially in open dry habitats. Such communities are often dominated by species of the genus Cladonia, which are very variable in morphology, reproduction strategies, and secondary metabolites. In this work, we investigated traits-environment relationships considering vegetation dynamics, substrate pH, disturbance, and climate. A total of 122 plots were surveyed in 41 acidic dry grasslands in the western Po Plain (Northern Italy). Relationships between Cladonia traits and environmental variables were investigated by means of a model-based Fourth Corner Analysis. Thallus morphology and metabolites responded to vegetation dynamics, substrate pH, disturbance, and climate, whereas reproduction strategies responded only to vegetation dynamics. Traits’ correlations with vegetation dynamics elucidate their colonization patterns in open dry habitats or suggest biotic interactions with bryophytes and vascular plants. In addition, correlations between metabolites and environmental factors support interpretations of their ecological roles. Our results also stress the importance of studying traits’ relationships with climatic factors as an alert towards lichen reactions to climate change.